Coronary Angiographic Findings in Acute Ischemic Stroke Patients With Elevated Cardiac Troponin: The Troponin Elevation in Acute Ischemic Stroke (TRELAS) Study. Issue 13 (29th March 2016) - Mochmann, Hans-Christian; Scheitz, Jan F.; Petzold, Gabor C.; Haeusler, Karl Georg; Audebert, Heinrich J.; Laufs, Ulrich; Schneider, Christine; Landmesser, Ulf; Werner, Nikos; Endres, Matthias; Witzenbichler, Bernhard; Nolte, Christian H.
Abstract : Background—: A relevant proportion of patients with acute ischemic stroke (AIS) have elevated levels of cardiac troponins (cTn). However, the frequency of coronary ischemia as the cause of elevated cTn is unknown. The aim of our study was to analyze coronary vessel status in AIS patients with elevated cTn compared with patients presenting with non–ST-segment–elevation acute coronary syndrome (NSTE-ACS). Methods and Results—: Among 2123 consecutive patients with AIS prospectively screened at 2 tertiary hospitals, 13.7% had cTn elevation (>50 ng/L). According to a prespecified sample size estimation, 29 patients with AIS (median age, 76 years [first–third quartiles, 70–82 years]; 52% male) underwent conventional coronary angiography and were compared with age- and sex-matched patients with NSTE-ACS. The primary end point was presence of coronary culprit lesions on coronary angiograms as analyzed by independent interventional cardiologists blinded for clinical data. Median cTn on presentation did not differ between patients with AIS or NSTE-ACS (95 versus 94 ng/L; P =0.70). Compared with patients with NSTE-ACS, patients with AIS were less likely to have coronary culprit lesions (7 of 29 versus 23 of 29; P <0.001) or any obstructive coronary artery disease (15 of 29 versus 25 of 29; P =0.02; median number of vessels with >50% stenosis, 1 [first–third quartiles, 0–2] versus 2 [first–third quartiles, 1–3]; P <0.01). Conclusions—: Coronary culprit lesions are significantly less frequent in AIS patients compared with age- and sex-matched patients with NSTE-ACS despite similar baseline cTn levels. Half of all AIS patients had no angiographic evidence of coronary artery disease. Further studies are needed to clinically identify the minority of patients with AIS and angiographic evidence of a culprit lesion. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01263964. Abstract : Supplemental Digital Content is available in the text.